ANALISIS NILAI KARAKTER CERITA RAKYAT SARIDIN YANG SAKTI DALAM BUKU CERITA RAKYAT - Anggita Mega Satria; Muhammad Raikhan Albani; Rif’an Ulin Nuha; Mohammad Kanzunnudin (Universitas Warmadewa, 2025)
The aim of this research is to analyze the values of the characters in the story Saridin Yang Sakti which is one of the few folk tales originating from the city of Pati in Central Java province. Folklore is a cultural heritage that has developed over time, as well as a learning method for generations of children that is passed on as the value of life. The method used to achieve the specified objectives is qualitative descriptive analysis. The data used in this research comes from popular literature books. The final aim of this research is to identify characteristics that can be used to identify role models and characteristics of figures that cannot be changed.